(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2024)
Bangladesh and India share 4096.7 km. land boundary, which was drawn between India and the eastern part of Pakistan (East Bengal) by the Radcliffe Award during the partition of 1947. This boundary became the Bangladesh-India boundary after the liberation of Bangladesh in 1971. Therefore, the Pakistan-India land boundary disputes over the un-demarcated boundary, adverse possessions and enclaves transformed into Bangladesh-India ones. These land boundary disputes witnessed one summit-level agreement between Pakistan and India and three summit-level agreements between Bangladesh and India. However, the land boundary disputes were eventually resolved under the land swap deal of 2015. This striking background led to the question as to why these issues were hung up for 68 years, what contexts led to several summit-level agreements on the same issues, and what were the correlations among the agreements. Against this background, this article attempts to shed light on how India, being the big neighbour, dominated the entire trajectory of the land boundary disputes and how it changed its agreed positions from one agreement to another. However, the main objective of this article is to see whether India’s territoriality towards its border with Bangladesh was gradually transformed into the pattern of a zero-sum game during the period from 1974 to 2015, and what was the corresponding territoriality of Bangladesh. Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 69(1), 2024, pp. 89-106